Assessment of the Quality of Life, Health, and Social Wellness in Upper Elementary School Students: Cross-Cultural and Gender Specificity - Ružena Popović; Evdokia Samouilidou; Jasna Popović; Milan Dolga (Britain International for Academic Research (BIAR) Publisher, 2020)
The objective of this study is a comparative analysis of the possibilities of physical education (PE) inclusion in children with health problems, and the current status in upper elementary school boys and girls. Understanding the concept of impaired health is a precondition for the realization of the training process and possible integration in the process of PE, according to the structure of health disadvantages. Method. Quality of life was assessed with the Questionnaire (Q), and analysis was done at three levels, with adequate methods of evaluation. Results. Comparative analysis, regarding the cultural and gender specificities is elaborated, based on MANOVA and DISCRA analysis, within the Introductory part, and 11 scales of the Q. Conclusion. Analysis of data points out on the significant cross-cultural differences, considering survey results, with a special overview of total samples of respondents (boys/girls) from diverse cultural, and social backgrounds.